Enhancing soil and pakcoy (Brassica rapa subsp. Chinensis) nutrient content: investigating the effects of chicken manure compost and bioactivator combinations on various doses - Trisia Wulantika; Yun Sondang; Rina Alfina; Ngakumalem Sembiring; Sentot Wahono; Wiwik Hardaningsih; Yefriwati; Ritawati; Febria Fitri (Universitas Lancang Kuning, 2023)
Chicken manure compost serves as a valuable source of organic fertilizer. This study aimed to investigate the effects of different combinations of chicken manure compost and bioactivators on soil and plant nutrient content. Additionally, it sought to examine the relationship between fertilizer dosage and soil and plant nutrient levels, as well as determine the optimal treatment combination of chicken manure compost and bioactivator variations at different doses. In this study, the plant used was pakcoy. The study utilized a randomized group design with two factors. The first factor involved different compost types: A1 (chicken manure compost), A2 (chicken manure compost + N21 bioactivator), and A3 (chicken manure compost + local microorganism (MOL) solutions from banana weevil). The second factor encompassed varying doses of organic fertilizer, 5, 10, 15, and 20 tons ha-1, respectively for D1-D4. The findings revealed that composting chicken manure with different bioactivators and doses led to increased soil nutrient levels and noticeable effects on plant nutrient content. However, no interaction was observed among the combined treatments. The treatment combination of chicken manure compost and MOL solutions from banana weevil yielded the highest average plant nutrient content. Applying chicken manure compost with different bioactivators and doses influenced soil nutrient levels.